Lunenburg - Baker, Keith (Headline Book Pub., 2001)
A young boy is witness to a horrific crime in Nova Scotia. Years later, journalist John Taggart is headed to Canada for a story, haunted by the mysteries of his past. When he meets Annie Welles, investigating two suspicious deaths, both become embroiled in a deadly conspiracy.